Analisis Sirah Nabi Saw Dalam Buku Teks Pendidikan Islam Tingkatan Satu Di Malaysia Berdasarkan Manhaj Al-muḥaddithīn - Kadir, Fadzlan Abd (2024)
Visual dialogue dataset, i.e. VisDial v1.0 includes a wide range of Microsoft Common Objects in Context (MSCOCO) image contents and collected questions via a crowdsourcing marketplace platform (i.e. Amazon Mechanical Turk). The use of existing question history and images no longer contributes to a better understanding of the image context as they do not cover the entire image semantic context. This research proposes the DsDial dataset, which is a context-aware visual dialogue that groups all relevant dialogue histories extracted based on their respective MSCOCO image categories. This research also exploits the overlapping visual context between images via adaptive relevant dialogue history selection during new dataset generation based on the groups of all relevant dialogue histories. It is half of 2.6 million question-answer pairs. Meanwhile, this research proposes Diverse History-Dialog (DS-Dialog) to resolve the missing visual semantic information for each image via context-aware visual attention. The context-aware visual attention includes the question-guided and relevant-dialoguehistory- guided visual attention modules to get the relevant visual context when both have achieved great confidence. The qualitative and quantitative experimental results on the VisDial v1.0 and DsDial datasets demonstrate that the proposed DS-Dialog not only outperforms the existing methods, but also achieves a competitive results by contributing to a better visual semantic extraction. DsDial dataset has proven its significance on LF model as compared to VisDal v1.0. Overall quantitative results show that DS-Dialog with DsDial dataset has achieved the best test scores for recall@1, recall@5, recall@10, mean rank, MRR, and NDCG respectively.